Skin Allergy to Azole Antifungal Agents for Systemic Use: A Review of the Literature - Calogiuri, Gianfranco; Garvey, Lene H.; Nettis, Eustachio; Romita, Paolo; Di Leo, Elisabetta; Caruso, Riccardo; Butani, Lavjay; Foti, Caterina (Recent Patents on Inflammation & Allergy Drug Discovery, 2019)
Background: Antifungal azoles are the first-line agents used to treat topical and, above all, systemic mycosis. The latter could be life-threating infections in immunocompromised patients. Chemotherapeutic antibiotics, including antifungal azoles, may induce hypersensitivity reactions; however, such immunologic adverse reactions have not been defined and carefully investigated. Objective: The study aims to provide an update on the evaluation and diagnosis of skin allergy to azole antifungal agents. Methods: This is a systematic review performed on PubMed and Google Schoolbarusing using the key terms “allergy, hypersensitivity, anaphylaxis, immediate-type reaction, delayed-type reaction, ketoconazole, fluconazole, posaconazole, voriconazole, itraconazole, triazoles, imidazoles, antifungals, antimycotics”. The search strategy included meta-analyses, randomized controlled trials, clinical trials, observational studies, reviews and case reports. Results: One hundred twenty-four articles matched our search terms. The most common adverse events reported were T-cell mediated delayed-type hypersensitivity reactions, fixed drug eruptions, exanthematous dermatitis, Steven-Johnson syndrome, toxic epidermal necrolysis and acute generalized exhanthematous pustulosis. Rarely a drug rash with eosinophilia systemic symptoms, has been described. Also, immediate-type reactions such as urticaria-angioedema or anaphylaxis have been reported following the administration of antifungal imidazoles, although not so frequently. Conclusion: Despite their widespread use, triazoles seem to induce rare cutaneous hypersensitivity reactions, but the pathomechanisms, risk factors, diagnostic and management strategies, including skin tests and challenge tests, are little known and poorly investigated.
Keywords: triazoles